PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEDISIPLINAN PEGAWAI DI KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN TAKALAR - Nur Firman; Nuryanti Mustari; Nurbiah Tahir (JPPM: Journal of Public Policy and Management, 2020)
This study aimed to determine and analyze the influence of transformational leadership style on employee discipline in the Office of Population and Civil Registry of Takalar Regency. This study used a descriptive study using quantitative methods and approaches that described the transformational leadership style of employee discipline in the Office of Population and Civil registry of Takalar Regency. The population in this study were all employees in the Office of Population and Civil Registry of Takalar  regency as many  as 50 people, civil servants were 30 people and 20 honorary. Sampling technique used saturated sampling. The results showed  that the transformational leadership style  had a positive and significant effect on employee discipline at the Office of Population and Civil Registration, with an R square coefficient of 0,524, meaning  52.4% of the leadership style affected employee discipline at the Office of Population and Civil Registration at Takalar Regency.